A Review of Articles on Infrastructure Contractors Financing in the Islamic Banking - Mohamad Torik Langlang Buana; Nuradli Ridzwan Shah Mohd Dali (Sekolah Tinggi Ilmu Ekonomi Muhamadiyyah Bandung, 2024)
Non-Indexed Publication